2021
DOI: 10.33549/physiolres.934662
|View full text |Cite
|
Sign up to set email alerts
|

Alternations in the cardiovascular autonomic regulation and growth factors in autism

Abstract: Autism spectrum disorder (ASD) represents a serious neurodevelopmental disorder associated with autonomic nervous system dysregulation. The aim was to study complex cardiovascular autonomic regulation using heart rate variability (HRV) and systolic blood pressure variability (SBPV) linear/non-linear analysis at rest and during orthostasis, and to assess plasma levels of epidermal growth factor (EGF) and vascular endothelial growth factor (VEGF) in autistic children. Twenty-five ASD boys and 25 age and gender-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…The barore ex is associated with some pathological conditions 48,51 , but only recently, imbalance of cardiac autonomic regulation in patients with intellectual disabilities and ASD is emerging [7][8][9][10][11][12][13][14][15][16][17][18][19] . However, the origins of dysautonomia in ASD is still unclear and somehow controversial with highly variable pro les depending on the studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The barore ex is associated with some pathological conditions 48,51 , but only recently, imbalance of cardiac autonomic regulation in patients with intellectual disabilities and ASD is emerging [7][8][9][10][11][12][13][14][15][16][17][18][19] . However, the origins of dysautonomia in ASD is still unclear and somehow controversial with highly variable pro les depending on the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Consequent to this genetic diversity, phenotypic characterization of the syndrome has often proven di cult, resulting in inconsistent conclusions. For instance, despite a paucity of information and con icting ndings in the literature, imbalance between the sympathetic and parasympathetic branches of the autonomic nervous system is commonly observed in ASD patients [7][8][9][10][11][12][13][14][15][16][17][18][19] . Overall, these studies point to a lower autonomic nervous system activity suggested to likely result from a decreased parasympathetic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Consequent to this genetic diversity, phenotypic characterization of the syndrome has often proven difficult, resulting in inconsistent conclusions. For instance, despite a paucity of information and conflicting findings in the literature, an imbalance between the sympathetic and parasympathetic branches of the autonomic nervous system is commonly observed in ASD patients 7 15 . Overall, these studies point to a lower autonomic nervous system activity suggested to likely result from a decreased parasympathetic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Consequent to this genetic diversity, phenotypic characterization of the syndrome has often proven difficult, resulting in inconsistent conclusions. For instance, despite a paucity of information and conflicting findings in the literature, imbalance between the sympathetic and parasympathetic branches of the autonomic nervous system is commonly observed in ASD patients [7][8][9][10][11][12][13][14][15][16][17][18][19] . Overall, these studies point to a lower autonomic nervous system activity suggested to likely result from a decreased parasympathetic activity.…”
Section: Introductionmentioning
confidence: 99%